2010
DOI: 10.1180/minmag.2010.074.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Diamond formation in the deep mantle: the record of mineral inclusions and their distribution in relation to mantle dehydration zones

Abstract: Studies of the inclusions contained in natural diamonds have shown the occurrence of minerals which must have formed at depths below the lithosphere and which may be closely matched with the silicate mineral assemblages determined by high pressure and temperature experimental studies for depths of 300 to 800 km in the Earth's mantle. The inclusions come principally from two main depth zones:(1) the lower asthenosphere and upper transition zone; (2) the Upper Mantle/Lower Mantle (UM/LM) boundary region and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(152 citation statements)
references
References 84 publications
(174 reference statements)
4
141
0
7
Order By: Relevance
“…Since conversion of metastable graphite to diamond is not expected to produce macrocrystals (Sung, 2000), diamond formation during a fluid/melt aided dissolution -precipitation process is likely. The volatile-rich nature of the protolith is consistent with the recent suggestion by Harte (2010) that ultradeep diamonds are associated with devolatilisation and possibly melting reactions. , the histogram on the X-axis is of cratonic diamonds (Stachel et al, 2009).…”
Section: This δsupporting
confidence: 74%
“…Since conversion of metastable graphite to diamond is not expected to produce macrocrystals (Sung, 2000), diamond formation during a fluid/melt aided dissolution -precipitation process is likely. The volatile-rich nature of the protolith is consistent with the recent suggestion by Harte (2010) that ultradeep diamonds are associated with devolatilisation and possibly melting reactions. , the histogram on the X-axis is of cratonic diamonds (Stachel et al, 2009).…”
Section: This δsupporting
confidence: 74%
“…As with majorite-bearing samples, the number of possible lower mantle diamond occurrences has grown since the initial discoveries, and examples are now recognised in South Africa (Moore et al 1986), Guinea (Stachel et al 2000b(Stachel et al , 2002, Canada (Davies et al 2004;Tappert et al 2005), Australia (Tappert et al 2009a, b) and Brazil, both from Machado river ) and the Juina region (see below). However, in contrast to majorite-bearing diamonds, the number of definitively lower mantle diamonds remains small and most of the diamonds are associated with peridotitic material (Harte 2010;Kaminsky 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, more than half of all recognised lower mantle diamonds are from Juina sources (Harte 2010), which makes Juina a unique geological locality. Studies of alluvial Juina diamonds (Harte et al 1999;Kaminsky et al 2001;Hutchison et al 2001;Hayman et al 2005;Brenker et al 2007) have revealed mineral inclusion assemblages associated with peridotitic material whilst the diamonds generally carry a "mantle-like" carbon isotope signature (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Fe 3+ is theoretically associated to the appearance of vacancies in non-stoichiometric wü stite and (Mg,Fe)O (Otsuka et al, 2010;Wdowik et al, 2015). Measured iron in Fe-periclase and bridgmanite, both coexisting as inclusions in lowermantle diamonds (Kaminsky and Lin (2017) (Harte, 2010;Kaminsky, 2012), the vacancy generation effect induced by ferric iron can therefore be assumed negligible in the present modelling.…”
Section: Deviations From Idealitymentioning
confidence: 99%